An efficient prediction model for vibrations induced by underground railway traffic and experimental validation. (November 2021) - He, Chao; Zhou, Shunhua; Di, Honggui; Zhang, Xiaohui
Abstract: This study proposes an efficient prediction model for the vibration generated by underground railways. The proposed model is based on an analytical approach for a tunnel in a horizontally multi-layered half-space, showing the advantage of high computational efficiency and accuracy. Three alternative modelling strategies regarding hypotheses about the cross-section behavior of the slab and the connection condition between the slab and tunnel are introduced. A multi-body vehicle model is subsequently coupled with the track-tunnel-ground system in the moving frame of reference to determine the train-induced vibration. The predicted vibrations on the track, tunnel, and ground surface induced by the passage of trains are compared with the measured vibrations from an underground railway line in London from the literature. The predicted results for the double-beam track model with uniform support and the continuum track model exhibit a good agreement with the site measurements. The cross-section deformation of the track can be ignored and has little influence on the responses of the tunnel and ground. However, the assumption of the one-line connection between the slab and tunnel results in an overestimation of the track vibration, up to 20 dB, and an underestimation of the tunnel and ground vibration, up to 10 dB.